Guru dan Problematikanya Serta Peran Organisasi Guru ( PGRI ) Provinsi Dki Jakarta dalam Memperjuangkan Nasib Guru SMA di Dki Jakarta (1998-2015) - Nurbaity Nurbaity; Rani Noviyanti; Yeni Handayani (Departement of Mathematics Education, 2023)
The Professional Association of Indonesian Teachers (PGRI) continues to fight for the welfare of teachers and educators, demonstrating a commitment to this cause. The PGRI DKI Jakarta Province is a key player in achieving its organizational goals. Through its mechanisms, the organization is able to effectively pursue its objectives. The organization is governed by its AD/ART, which oversees meetings at the national and local level focused on policymaking for improving teacher welfare. Since the formation of the Law on Teachers and Lecturers in 2005, which provides a legal basis for demands for improved teacher welfare, the struggle for better working conditions for teachers has intensified. There are not only demands for teacher professional allowances, but also struggles for local governments and other related institutions, such as regional allowances, grants, self-protection (such as in the collaboration between POLRI and PGRI), housing, and so on. The teacher's professional position and dignity are important considerations when making decisions about what to do in the classroom